Social-Economic Problems in Latvia in the Context of the Members of Europe Union - Литвиненко, Алина; Зайцева, Евгения (Ekonomika, 2004)
In the article questions of a social and economic situation in Latvia on the background of the countries-participants of the European Union are considered (Latvia became a member of the European Union on May, 1, 2004). The author pays attention to the main parameter, describing a condition of a national economy - to inflation and changes of value rates in comparison of these parameters with other countries of Baltic Region (Lithuania and Estonia). In this article the main reasons of inflation process also are revealed. One of the most important nowadays question for all countries-members of European Union is global cross-rates. It is known that costs growth; development of manufacture; savings in the bank and so on are depend on global cross-rates. It is a pity, but for nowadays Latvia according most of economical factors takes the lowest position among all 25 countries-members of European Union. The situation with an internal total product, wages, foreign trade, foreign investments, prospects of use of structural European funds and achievements of European Union advanced countries level is analyzed.